EVALUASI KESESUAIAN LAHAN PENGEMBANGAN KOMODITI TANAMAN PANGAN BERBASIS SPASIAL DI KEC. TANETE RIAJA, KAB. BARRU - Samsuar; Muhammad Tahir Sapsal; Mahmud Achmad; Husnul Mubarak; Nunik Lestari (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2020)
Increasing land productivity, especially in the agricultural sector, are absolutely necessary at this time. One effort that can be done is by evaluating the characteristics of the land in order to obtain suitable information for the development of agricultural commodities in an area. The purpose of this study was to provide information on land characteristics and to analyze the level of land suitability for the development of food crop commodities (rice, corn, soybeans and cassava). The land characteristic parameters observed included climate, land morphology, soil physical and chemical properties. The results show that it is possible to develop food crops in Tanete Riaja District, even though only in the S2 and S3 categories. The slope factor is the main obstacle in the development of this commodity, so that crop management such as terracing and intercropping systems is an alternative cropping model that can be implemented. Low soil fertility and acidic soil pH are manageable factors that can be improved to increase soil quality.